IMPLEMENTASI METODE PROTOTYPE PADA PERANCANGAN SISTEM INFORMASI WEB: SOLUSI MENINGKATKAN PELAYANAN DAN EFISIENSI LRT DI KOTA PALEMBANG - Fenny Purwani; Almahira Muti’a Zakia; Muhammad Indra Irillah; Faza Intaniansyah (Jurnal Riset Teknik Komputer, 2024)
Public transportation, especially Light Rail Transit (LRT), plays a vital role in supporting community mobility and economic growth. In Palembang, the LRT system is the main means of transportation that facilitates social interaction and efficient movement of goods. However, this service faces challenges such as not utilizing current technological advances or still relying on cash transactions and member cards that are vulnerable to loss, long queues at counters that cause a waste of time and limited access to real-time information.This research aims to implement the prototype method in developing a web information system to improve the service and efficiency of LRT in Palembang City. The proposed system will provide innovative features, including online ticket booking, problem reporting, and real-time train schedule tracking. The prototype method will be applied through the stages of requirements gathering, initial prototype design, user evaluation, and iterative system improvement. It is expected that the implementation of this system can increase the effectiveness of LRT services, simplify the ticket booking process, and accelerate access to information for users. This research aims to make a significant contribution in improving the quality of public transportation services in Palembang through the integration of information technology in the LRT system.